The influence of the bimodal stimulation on the auditory ability of temporal ordering - Maria Madalena Canina Pinheiro; Patrícia Ilsi Welter; Jaqueline Cardoso Estácio (Revista CEFAC, 2020)
ABSTRACT Objective: to analyze temporal ordering auditory ability in unilateral cochlear implant users with bimodal stimulation. Methods: the study included 15 unilateral cochlear implant users, six with bimodal stimulation and nine with exclusive cochlear implant and a control group consisting of 15 hearing individuals. Both groups underwent the standard duration and the standard frequency tests for temporal ordering auditory ability analysis. In the inferential analysis of the data, the nonparametric statistical tests Mann-Whitney and Kruskal-Wallis were used (p<0,05). Results: there was a significant difference in the performance of the standard frequency test, and subjects with bimodal stimulation presented a better performance than those with exclusive cochlear implants. The standard frequency test was associated with education and speech therapy. On the other hand, in the standard duration test, there was a relation with the implanted ear. The most frequent errors were discrimination for both temporal tests. Conclusion: bimodal stimulation, education and speech therapy influenced the performance of the frequency pattern test, while the implanted side influenced the performance of the duration pattern test.